Method for depolymerizing hybrid automotive plastics

By sorting and depolymerizing mixed automobile plastic waste, the problem of pyrolytic oil pollution in the existing technology is solved, and efficient conversion into low-pollution depolymerization products suitable for crackers is achieved, thereby enhancing the recycling value of waste.

CN119546686APending Publication Date: 2025-02-28BASELL POLIOLEFINE ITALIA SRL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053290.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-08-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively convert hybrid automotive plastic waste into liquid or gaseous pyrolytic products that can be used as cracker fuel or feedstock, and pyrolytic oils are not suitable for fuel applications due to high heteroatomic and halogen contamination.

Method used

By sorting automotive plastic waste to obtain a high content of polyethylene and polypropylene mixture, after mincing or granulation, depolymerization is depolymerized at 300-500°C in the presence of a catalyst to obtain a gaseous depolymerization product and separated into a liquid and a gaseous stream by condensation.

Benefits of technology

It realizes the conversion of mixed automobile plastic waste into low-pollution liquid and gaseous depolymerization products, suitable for cracker feed or clean fuel, reducing pollutant content and improving product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237717230000111
    Figure BDA0005237717230000111
  • Figure BDA0005237717230000161
    Figure BDA0005237717230000161
  • Figure BDA0005237717230000171
    Figure BDA0005237717230000171
Patent Text Reader

Abstract

A method of recovering automotive plastic waste comprising: (i) sorting said automotive plastic waste (APW) to obtain a plastic waste fraction comprising at least 60 wt.% of a mixture of polyethylene (PE) and polypropylene (PP); (ii) chopping and / or granulating the part to obtain a plastic raw material with the bulk density higher than 100g / l; (iii) depolymerizing the feedstock at 300-500 DEG C in the optional presence of a catalyst, thereby obtaining a gaseous depolymerized product, and (iv) collecting the gaseous depolymerized product and separating it into liquid and gaseous streams.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the depolymerization of polymer waste materials. More specifically, the present disclosure relates to a method for depolymerizing mixed automotive plastic waste by thermocatalytic degradation. Background Art

[0002] Mixed post-consumer plastic waste from automotive applications is generated globally in large quantities through repair and recycling of end-of-life vehicles. Due to the wide variety of polymers used in automobiles, as well as the use of many plastic / metal composites and plastic / inorganic filler composites, purely mechanical reprocessing of these plastics is not possible or practical with reasonable energy and labor expenditure.

[0003] Scrapped cars are shredded and sorted in scrap car recycling plants to retain mainly the metals that are returned. As another stream, a plastic waste fraction is also obtained. However, due to the high contamination, these automotive plastic waste streams are usually incinerated for energy recovery (quaternary recycling). However, these wastes can also be treated by chemical recovery (also called tertiary recycling) technologies and in particular by pyrolysis.

[0004] The pyrolysis of mixed and unsorted automotive plastic waste results in pyrolysis oils that are contaminated with heteroatoms and very high levels of halogens. Due to the high levels of these contaminants, the corresponding pyrolysis oils are unsuitable for fuel applications and for use as feedstock for steam crackers.

[0005] Therefore, there is a need for a method of converting mixed automotive plastic waste into liquid or gaseous pyrolysis products that can be used as fuel or feedstock for a cracker.

[0006] A plastic waste fraction was generated from post-consumer mixed automotive waste with a polyolefin content > 70 wt.% by developing a method for identification and separation of highly contaminated automotive plastic parts. The quality of the pyrolysis oil obtained from this separated fraction was shown to have a low content of heteroatoms, halogens and aromatic compounds. Summary of the invention

[0007] In one aspect, the present disclosure provides a method for recycling automotive plastic waste, comprising:

[0008] (i) sorting the automotive plastic waste (APW) to obtain a plastic waste fraction comprising a mixture of at least 60 wt.% of polyethylene (PE) and polypropylene (PP);

[0009] (ii) chopping and / or granulating the portion to obtain a plastic material having a bulk density greater than 100 g / l;

[0010] (iii) depolymerizing the feedstock at 300-500° C. in the optional presence of a catalyst to obtain a gaseous depolymerization product, and

[0011] (iv) collecting the gaseous depolymerization product and separating it into liquid and gaseous streams. DETAILED DESCRIPTION

[0012] In a preferred aspect of the present disclosure, the sorting of APW allows to obtain a fraction with a content of PE and PP higher than 70%, more preferably higher than 75%. In this respect, the term polyethylene includes all members of the polyethylene family, such as high density polyethylene (HDPE), medium density polyethylene (MDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ultra low density polyethylene (ULDPE) and plastomers and elastomers made of ethylene with butene-1, hexene-1 or octene-1 or combinations thereof as comonomers. Likewise, the term polypropylene (PP) includes propylene homopolymers, copolymers of propylene with other α-olefins and so-called heterophasic copolymers (HeCO), which include a crystalline part of a propylene homopolymer or copolymer and an elastomeric amorphous part, usually made of propylene / ethylene copolymers.

[0013] The sorting part may also include the above PP and PE polymers filled with inorganic materials such as talc, silica, glass fibers or glass beads.

[0014] Preferably, the amount of non-olefin polymers is less than 5 wt.%, preferably less than 3 wt.%, more preferably less than 2 wt.%, and especially completely absent, wherein the term refers to polymers derived from monomers comprising heteroatoms. Examples of such non-olefin polymers are polyamides (PA), polycarbonates (PC), polyethylene terephthalate (PET), acrylonitrile styrene acrylate (ASA), polyoxymethylene (POM), acrylonitrile butadiene styrene (ABS) and halogenated polymers.

[0015] Furthermore, in a very preferred embodiment, the metal-rich fraction is removed and thus the cumulative amount of metals selected from iron, copper, aluminum, magnesium, chromium in the sorted feed fraction is below 1 wt.%, preferably from 0.1 wt.% to 0.7 wt.%, or is completely absent.

[0016] The above-mentioned selected fraction constitutes a feedstock suitable for recovery purposes, in particular for use as a feedstock for a depolymerization process.

[0017] Sorting

[0018] A variety of techniques are known for separating materials in a polymer waste material stream. Moving beds, drums and screens, and air separators are used to distinguish materials by size, weight, and density. Depending on the nature of the raw materials, the sorting techniques may vary and may be manual or automatic. In particular, automated separation techniques for waste plastics include dry sorting techniques, electrostatic sorting techniques, mechanical sorting methods (involving centrifugal force, specific gravity, elasticity, particle shape, selective shredding, and mechanical properties), as well as wet sorting techniques (e.g. sink-float sorting methods) and chemical sorting methods.

[0019] When the APW feedstock is derived from ELV scrap, ferrous metal parts and cables can be removed manually or by magnetic separators. Non-ferrous materials, such as aluminum, copper and zinc, can be separated by eddy current separators, such as commercially available separators based on an eccentrically mounted pole system.

[0020] In an alternative approach, density-based separation can be used to separate particles with densities above 2.5 g / cm 3 The metal part is thus obtained with a density lower than 2.0 g / cm 3 This fraction is subjected to a further density separation step to separate the plastic-rich fraction with a density below 1.06 g / cm 3 of the polyolefin-rich fraction.

[0021] Repair shops offer an alternative source of APW. When processing APW from this source, sorting can be based on the specific polymer, density, and typical applications of polymer composites of a specific composition. As an example, density <1.0 g / cm 3 Colorless tanks (e.g. cooling water expansion tanks) can be assigned to the polyethylene part, while density <1.0g / cm 3 The black fuel tank and black fuel hose may be associated with parts of halogenated materials.

[0022] Typically, dimension > 10 cm along one axis and density < 1.06 g / cm 3 Unpainted exterior parts such as wheel arch linings, wheel arch panels and bumper rails are made from PP talc and mineral-filled parts and therefore turn to PP talc and mineral-filled parts.

[0023] Dimension > 10 cm along one axis and density 1.06-1.3 g / cm 3 Unpainted exterior parts such as wheel house linings, wheel arches and bumper rails can be distributed into the non-polyolefin part including ASA, ABS, PC / ABS, POM part according to the material imprint on the parts after manual separation of the polyamide parts, which are collected separately in the PA part.

[0024] Dimension > 10 cm along one axis and density 1.06-1.3 g / cm 3 The engine hood is also preferably designated as a PA part.

[0025] Raw material handling

[0026] The sorted APW is processed by shredding and / or granulation in a manner to make the particle size uniform and to achieve a bulk density of more than 100 g / cm 3 , preferably higher than 300g / cm 3 , more preferably higher than 500g / cm 3 The value of .

[0027] In particular, in larger scale operations, the polymer waste material feedstock may be in the form of particles, e.g., particles having a particle size of 1 to 20 mm, preferably 2 to 10 mm, more preferably 2 to 8 mm, or in the form of shredded flakes and / or small pieces of film, preferably with a particle size of 1 to 100 mm. In the context of the present disclosure, having a particle size within a defined range means that 90 wt% of the particles have a particle size within a defined range. The particle size may be determined by sieving or by using a Beckman Coulters LS13320 laser diffraction particle size analyzer.

[0028] The sorted APW may optionally be extruded prior to use as a feedstock in the process of the present disclosure.In a preferred embodiment, the sorted APW is pelletized and the pellets are used as a feedstock in the process of the present disclosure.

[0029] Depolymerization method and reactor

[0030] The depolymerization may be carried out in the presence or absence of a catalyst and at a temperature of 300 to 550°C, more preferably 350 to 500°C.

[0031] In its basic aspect, the sorted and treated APW and optionally the catalyst are introduced into the depolymerization unit and then heated to the above-mentioned temperature to achieve depolymerization. The gaseous part produced during the depolymerization process is discharged and sent to a condensation unit, from which a liquid stream and a gaseous stream are obtained. Any solid residue of the depolymerization is discharged via a solid discharge unit.

[0032] The obtained liquid depolymerization product may be further separated. Therefore, the method of the present disclosure may further comprise the step of distilling the liquid depolymerization product.

[0033] The method of the present disclosure can produce a depolymerization product with a high gaseous content. In particular, the gaseous content in the depolymerization product can be 20 to 60% based on the total weight of the gaseous and liquid depolymerization products.

[0034] The gaseous part of depolymerization product, particularly when using depolymerization catalyst, preferably has high content of monomer olefinic C2-C4-compound, it is particularly useful for further processing, for example, for producing polymkeric substance.Owing to produce a large amount of this compound in depolymerization process, gaseous depolymerization product can be directly used as raw material in cracking method and subsequent polymerization.The gaseous product comprising light olefins and light alkanes can be for example transferred to downstream cracker to produce polymerization grade monomer stream by baking oven.Other by-products such as ethane, propane and butane will be cracked in baking oven.Therefore can bypass the step of obtaining the product of required monomer after the treatment depolymerization that is usually needed, save valuable energy and reduce CO2 output.

[0035] The depolymerization process according to the present disclosure can be carried out in a reactor comprising: (a) a feeding device for introducing polymer waste materials and a catalyst into the reactor; (b) a pyrolysis device equipped with a heating unit, a gas discharge unit and a solid discharge unit; and (c) a condensing device.

[0036] In a preferred embodiment, the reactor may comprise more than one pyrolysis unit.

[0037] In principle, any type of reactor for pyrolysis can be used. It can be, for example, a stirred vessel with rotating blades or, preferably, a horizontal reactor, equipped with a screw for uniformly mixing the polymer waste in the pyrolysis device throughout the depolymerization process. The residence time of the solids in the pyrolysis device can be clearly defined by adjusting the rotation speed of the screw.

[0038] In such a reactor, a gas discharge unit is distributed throughout the pyrolysis device and is provided with an outlet for discharging the depolymerized gaseous fraction and an inlet for introducing clean gas into the pyrolysis device.

[0039] Preferably, the gas discharge unit is equipped with a filter membrane to avoid the presence of solids in the gaseous part after discharge from the pyrolysis device.The gas discharge unit is preferably made of metal or ceramic granules or fiber materials.

[0040] In a preferred embodiment, the condensing device comprises several condensers which are preferably operated at different temperatures. The temperature of the condenser can be set according to the boiling point of the condensate.

[0041] Depolymerization catalyst

[0042] Although the depolymerization process of the present disclosure can work with purely thermal depolymerization, employing a depolymerization catalyst is a preferred embodiment.

[0043] According to the present disclosure, the catalyst can be selected from those that are active as depolymerization / cracking catalysts in thermal catalytic processes. In particular, it can be selected from metal oxides, heteropolyacids, mesoporous silica, aluminosilicate catalysts, such as halloysite and kaolinite, and is preferably selected from zeolites. Among them, particularly preferred zeolites are synthetic Y-type zeolites and ZSM-5.

[0044] A preferred specific type of catalyst comprises as active component an acidic compound which is deposited on a particulate nonporous support with the aid of a coating agent.

[0045] It was found that the catalyst, in addition to being highly effective in depolymerization, can be easily separated from any solid residues of the depolymerization process, thereby allowing multiple uses.

[0046] The above catalyst is preferably in granular form. It is preferably a granular non-porous carrier selected from sand, glass beads and metal particles. The granular non-porous carrier can have any shape, such as spherical, cylindrical or any non-uniform shape. In addition to being granular, the carrier used in the catalyst of the present invention is also non-porous. Within the meaning of the present disclosure, non-porous should be understood as impermeable to gases (such as air) or liquids (such as water). In order to make the catalyst of the present disclosure specially designed to be mixed with polymer waste materials undergoing depolymerization, the carrier preferably has an average particle size D50 of 0.2mm to 20mm, preferably 0.5mm to 10mm, more preferably 1mm to 8mm, most preferably 1mm to 6mm determined according to sieve analysis according to ISO 3310-1 / ASTM E11. With a wire mesh screen The Retsch test sieve apparatus is an example of a useful sieving device.

[0047] Sand is a preferred type of non-porous particulate support.

[0048] The acidic compound of the catalyst of the present disclosure is preferably selected from the group consisting of: Al / Si mixed oxide, Al2O3, aluminosilicate, silica and zeolite. The Al / Si mixed oxide particularly preferred in the present disclosure refers to a material having a neutral structure containing a mixture of Al2O3 and SiO2.

[0049] Zeolites as referred to in this disclosure are understood to be crystalline microporous aluminosilicates consisting of zeolites having the general structure M n +x / n[AlO2]-x(SiO2) y ]+zH2O corner-sharing SiO4- and AlO4- tetrahedra, wherein n is the charge of the cation M, which is usually an alkali metal or alkaline earth metal or a hydrogen ion, preferably selected from H + 、Na + , Ca2 + , K + and Mg2 +ions, and z defines the number of water molecules incorporated into the crystal structure. Zeolites differ from mixed Al / Si oxides in that they define pore structures and ionic properties. In a particularly preferred embodiment, the zeolite used as an acidic compound is selected from zeolite Y, zeolite β, zeolite A, zeolite X, zeolite L and mixtures thereof, particularly zeolite Y and zeolite β. The zeolites listed are well known and commercially available. Particularly preferred are zeolites in which the metal ion M is replaced by hydrogen. Other specific examples of suitable zeolite-type components for the present disclosure include, but are not limited to, ZSM-5, ZSM-11, ZSM-22, ZSM-23, ZSM-35, ZSM-48, ZSM-50, TS-1, TS-2, SSZ-46, MCM-22, MCM-49, FU-9, PSH-3, ITQ-1, EU-1, NU-10, silicalite-1, silicalite-2, boronite-C, boronite-D, BCA and mixtures thereof.

[0050] In a particularly preferred embodiment, the acidic compound is an Al / Si mixed oxide. The composition of the Al / Si mixed oxide used as a carrier can be adjusted as required. However, the result of depolymerization is particularly good when the acidic compound contains a specific amount of Al O and SiO. Therefore, in a preferred embodiment, the Al O contained in the acidic compound in an amount of 20-99wt%, preferably 30-80wt%, especially 40-70wt%, based on the gross weight of the acidic compound. In addition, the acidic compound preferably contains 1-80wt%, preferably 20-70wt%, especially 30-60wt% SiO based on the gross weight of the acidic compound.

[0051] The SiO2 and Al2O3 contents of the acidic compound can be determined by atomic emission spectrometry using inductively coupled plasma (ICP-AES).

[0052] The coating agent used in the catalyst of the present disclosure is preferably selected from oil, inorganic hydrogel or a combination thereof. As inorganic hydrogel, silica hydrogel is preferred. As for the oil used as coating agent, aromatic-free white mineral oil, preferably based on isoparaffin, is preferred. In a preferred embodiment, the kinematic viscosity of the oil used at 20° C. is 140-180 mm 2 / s, preferably 150-170mm 2 / s, and / or a kinematic viscosity of 40-80 mm at 40°C 2 / s, preferably 50-70mm 2 / s, and / or a kinematic viscosity of 5-15 mm at 100°C 2 / s, preferably 7-10mm 2 / s. The kinematic viscosity can be determined according to ISO 3104.

[0053] The preferred amount of coating agent is 1-300%, preferably 2-150 wt%, more preferably 5-100 wt%, most preferably 10-80 wt%, based on the amount of acidic compound.For hydrogels, the amount to be employed refers to dry weight.

[0054] In another preferred embodiment, the active compound is included in the catalyst of the present disclosure in an amount of 0.5 to 6 wt %, preferably 2 to 4 wt %, based on the total weight of the catalyst.

[0055] The above catalyst is preferably obtained by mixing a granular non-porous support and a coating agent, and then adding a powdered acidic compound to the resulting mixture. The mixture may optionally be heat treated to obtain the catalyst. The heat treatment may be carried out, for example, at a temperature of 100 to 600° C. In a preferred embodiment, the granular non-porous support undergoes a drying step before mixing with the coating agent.

[0056] In particular when component (c) is selected from hydrogels, the catalyst can be reactivated by heating, thereby allowing multiple uses and saving resources. In a preferred embodiment, the catalyst can therefore be reactivated by heat treatment.

[0057] Depolymerization products

[0058] The gaseous fractions produced during the pyrolysis are separated, for example by condensation, into liquid and gaseous depolymerization products.

[0059] Liquid depolymerization product

[0060] The obtained liquid depolymerization product may show a low content of aromatic compounds, in particular a low content of polycyclic aromatic compounds and asphaltenes. Thus, the liquid depolymerization product obtained by the process of the present disclosure is characterized by a low content of aromatic and olefinic components and a high purity.

[0061] Preferably, the liquid depolymerization product obtained has an aromatic content of less than 10 mol%, preferably less than 5 mol%, in particular not more than 3 mol%, the content of aromatic components being measured as the content of aromatic protons in mol% determined by 1H-NMR spectroscopy.

[0062] In addition, the liquid depolymerization product obtained by the depolymerization process of the present disclosure is characterized by a low content of olefinic compounds. The content of olefinic compounds in the liquid depolymerization product is preferably less than 7 mol%, more preferably less than 5 mol%, and even more preferably less than 3 mol%, based on the total number of hydrocarbon protons; the content of olefinic compounds is determined based on the content of olefinic protons determined by 1H-NMR spectroscopy.

[0063] Another measure of the double bond content in a given sample is the bromine number (Br No.), which indicates the degree of unsaturation. In a preferred embodiment, the liquid depolymerized product obtained by the process of the present disclosure has a bromine number of less than 150, preferably 10 to 100, more preferably 15 to 80, even more preferably 20 to 70, especially 25 to 100, measured according to ASTM D1159-01, expressed as grams of bromine / 100 grams of sample.

[0064] The liquid depolymerization product obtained in the process of the present disclosure preferably has a boiling range of 30 to 650° C., more preferably 50 to 250° C. By separation techniques such as distillation, the depolymerization product can be separated into hydrocarbon fractions with different boiling ranges, for example, a light naphtha fraction mainly containing C5 and C6 hydrocarbons with a boiling range of 30° C. to 130° C., a fraction mainly containing C6 and C6 hydrocarbons with a boiling range of 130° C. to 220° C., and a fraction mainly containing C7 and C8 hydrocarbons with a boiling range of 150° C. to 220° C. 12 The heavy naphtha fraction of hydrocarbons mainly contains C9 and C 17 The kerosene fraction of hydrocarbons may be separated into other high boiling fractions such as diesel fuel, heating oil or wax oil.

[0065] Preferably, the liquid depolymerization product contains little to no solid residues. In a preferred embodiment, the liquid depolymerization product has a residue content of no more than 5 ppm (w) upon evaporation as determined according to ASTM D381.

[0066] Gaseous depolymerization products

[0067] The obtained gaseous depolymerization product may show a low content of low molecular weight hydrocarbons such as methane or ethane. On the contrary, it is preferred to have a higher amount of olefins such as ethylene, propylene and butene, which are generally required for polyolefin production. Therefore, the gaseous depolymerization product obtained by the process of the present disclosure is characterized by a high content of any one of ethylene, propylene and butene and / or a low content of saturated low molecular weight hydrocarbons, especially those of the general formula C n H 2n+2 wherein n is a real number from 1 to 4.

[0068] Therefore, in a preferred embodiment, the gaseous depolymerization product of the process of the present disclosure is characterized in that the methane content is at most 6 wt%, preferably at most 4 wt%, more preferably at most 3 wt%, most preferably at most 2 wt%, in particular at most 0.5-1.5 wt%, based on the total weight of the gaseous depolymerization product after step (e) of the process of the present disclosure.

[0069] Preferably, the gaseous depolymerization product obtained by the method of the present disclosure contains a large amount of low molecular weight olefinic compounds, especially C n H 2nspecies, wherein n=2-4. The gaseous portion can thus be used directly as a feedstock for further processing in a cracker downstream (e.g., a feed gas compressor) to obtain a purified monomer stream and thereafter for subsequent polymer production, thereby allowing bypassing the energy-intensive stream cracking furnaces that are usually required, while reducing the output of CO2. Therefore, in a preferred embodiment, the gaseous depolymerization product of the process of the present disclosure is characterized in that, based on the total weight of the gaseous depolymerization product after step (e) of the process of the present disclosure, the general formula C n H 2n The content of compounds of (olefins) (wherein n=2-4) is at least 50 wt%, preferably at least 60 wt%, more preferably at least 65 wt%, most preferably at least 70 wt%, especially at least 75 wt%.

[0070] The gaseous depolymerization products may contain small amounts of HCl, HCN, H2S, H2O, NH3, COS, etc., which may optionally be separated in a refining step before introduction into the downstream section of the steam cracker.

[0071] As explained, the depolymerization process of the present disclosure results in a liquid depolymerization product with low contaminants that is suitable for use as a steam cracker feed or fuel.

[0072] In particular, the step of sorting post-consumer automotive waste allows:

[0073] - Reduce pollutants to improve catalyst efficiency;

[0074] - Obtain high product quality products with low contaminant content (N, S, Cl, metals) for direct use as steam cracker feed and / or clean fuel;

[0075] - To enable the recovery of a higher fraction of the material as metals and as engineering plastics PCR for mechanical recycling;

[0076] - Obtaining high yield of gaseous products rich in light olefins;

[0077] - low residue / coke by-product from depolymerization;

[0078] - Easy recovery of fillers from residues into recycled materials.

[0079] The present disclosure will be explained in more detail with reference to the drawings and examples provided below.

[0080] Example

[0081] The following analytical methods were used:

[0082] 1) GC MS is used for liquid and gas phase analysis.

[0083] 2) After decoking the reactor residue at 800° C., the carbon residue was determined based on a mass balance.

[0084] 3) Liquid content was characterized using simulated distillation (SimDist) analysis according to ASTM D 7213: 2012. Final boiling point (FBP), boiling temperature at 50%, and initial boiling point (IBP) were taken from SimDist.

[0085] 4) The total content of unsaturated components in the liquid condensate was characterized by bromine number determination using an 848 Titrino Plus (Metrohm AG, Herisau, Switzerland) equipped with a double PT wire electrode with an integrated PT1000 temperature sensor and a 10 ml burette according to ASTM D1159-01 as described in Metrohm Application Bulletin 177 / 5e, December 2018. The bromine number (Br No.) indicates the amount of bromine absorbed by 100 grams of sample in grams.

[0086] 5) 1H-NMR analysis was performed by dissolving a sample of the liquid condensate in CDCl3 and characterizing the sample using proton NMR spectroscopy. Aromatic, olefinic and aliphatic protons were assigned according to the chemical shifts summarized in Table 1:

[0087] Table 1-1 Integration area in H-NMR spectrum

[0088] Peak attribution 1H chemical shift (ppm) <![CDATA[I1 (Aromatic protons)]]> 8.25-7.27 <![CDATA[CDCl3 - Solvent]]> 7.26 <![CDATA[I2 (aromatic protons)]]> 7.25-6.60 <![CDATA[I3 (olefinic proton - type 2)]]> 6.60-5.95 <![CDATA[I4 (olefinic proton - type 1)]]> 5.95-5.67 <![CDATA[I5 (olefinic proton - type 2)]]> 5.67-5.35 <![CDATA[I6 (olefinic proton - type 3)]]> 5.35-5.15 <![CDATA[I7 (olefinic proton - type 1)]]> 5.15-4.85 <![CDATA[I8 (vinylic proton - type 4)]]> 4.85-4.40 <![CDATA[I9…(Protons of alkane)]]> 4.40-0.25

[0089] The listed types of olefinic protons are assumed to correspond to the following structures:

[0090]

[0091] The amount of aromatic, olefinic, and aliphatic protons can be determined based on the specified peak integrations according to the following equations:

[0092] Aromatic proton mol% = [(I1+I2) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0093] Olefinic proton type 1 mol% = [(I4+I7) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0094] Olefinic proton type 2 mol% = [(I3+I5) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0095] Olefinic proton type 3 mol% = [(I6) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0096] Olefinic proton type 4 mol% = [(I8) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0097] Alkane proton mol% = [(I9) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0098] 6) The water content of the catalyst was determined at 180° C. on 0.5-1 g samples using a Sartorius MA45 (Sartorius AG, Goettingen, Germany).

[0099] 7) To determine the pH value of the hydrodepolymerization product, a liquid sample of the hydrodepolymerization product was extracted with water at a water:sample volume ratio of 1:5, and the pH value of the aqueous solution was measured.

[0100] 8) The particle size distribution of the particulate non-porous support and catalyst was determined by Coulter Counter analysis according to ASTM D4438.

[0101] 9) The properties of the organic waste materials used are determined as follows:

[0102] Since the composition of organic waste materials can vary, grind and analyze 20 to 100 g samples of polymer waste. Alternatively, analyze a pelletized sample of polymer waste. Use the following method:

[0103] i) Total volatiles (TV) was measured as the weight loss of a 10 g sample after 2 hours at 100° C. and 200 mbar.

[0104] ii) The water content was determined by Karl-Fischer titration according to Metrohm Application Bulletin 77 / 3e in accordance with ASTM E203 using an apparatus from Metrohm 915KF Ti-Touch equipped with a PT100 indicator electrode for volumetric KF titration.

[0105] iii) IR-spectroscopy is used for qualitative identification of various polymers (PP, PE, PS, PA, PET, PU, ​​polyester) and additives like CaCO3.

[0106] iv) Standard elemental analysis was used to determine the wt% of H, C, N (DIN 51732:2014-07) and S (tube furnace, ELTRA GmbH, Haan, Germany, DIN 51724-3:2012-07).

[0107] v) 1H-NMR is used to determine the composition of polymers soluble in a solvent sufficient for recording the 1H-NMR spectrum: PE / PP equilibrium (also copolymers), PET, PS.

[0108] vi) Ash content analysis of plastics is determined at 800 °C in accordance with DIN EN ISO 3451-1 (2019-05).

[0109] vii) Determination of bulk density of polymer waste in accordance with DIN 53466.

[0110] viii) Corrosivity was determined as the pH value of the aqueous solution after a contact time of 3 hours (5 g sample in 50 ml distilled water)

[0111] ix) Inductively coupled plasma atomic emission spectrometry (ICP-AES) for quantitative elemental determination (total chlorine content, Si or metal content)

[0112] x) The ash content of liquid feedstock such as pyrolysis oil is measured according to ASTM D482-19.

[0113] Catalyst 1

[0114] The catalyst was prepared as follows:

[0115] 25.0kg of sand is placed in a 60L steel drum with a screw cap and equipped with a Teflon inlay. 500ml of water (corresponding to 2.0wt% relative to the sand) is added, and the drum is placed on a drum hoop mixer and rotated for 1 hour (about 100rpm). 24.5kg of the resulting mixture is placed in another drum, and 1000g of a 1:1 ground free-flowing silica hydrogel and a mixture of zeolite beta as an acidic compound (equivalent to a loading of 2wt%) are added. The drum is placed on a drum hoop mixer and rotated for 1 hour (about 100rpm). At the end of the mixing process, a free-flowing catalyst is obtained, in which the particles of the acidic compound are evenly distributed on the surface of the sand particles. The obtained mixture is vacuum dried at 120°C for 6h.

[0116] The silica hydrogel was prepared according to Example 1 of EP 1290042. The solid content of the hydrogel sample was 20 wt%. The D50 of the ground mixture of silica hydrogel and acidic component was 80-100 μm according to ASTM D4438.

[0117] The sand used had the particle size distribution summarized in Table 1 below, where 99% of the particles were smaller than 3 mm. Before being used to form the catalyst, the sand was predried in a drying cabinet with circulating air at 80° C. for 24 h.

[0118] Table 1: Particle size distribution

[0119] Sand, wt% >1400μm 40.55% >1400μm->1000μm 55.30% <1000μm 4.15%

[0120] Zeolyst β (CP811E-75), commercially available from PQ Corporation, Malvern, PA, USA

[0121] Catalyst 2

[0122] The catalyst was prepared using the same procedure as described for Catalyst 1, except that silica hydrogel was not used as the coating agent.

[0123] raw material

[0124] The following APW-containing materials were obtained as raw materials:

[0125] Comparison with raw material A

[0126] Scrapped cars are shredded in scrap car recycling facilities. Most metals (density > 2.5g / cm 3 ) are separated by magnetic and / or density separation to obtain a plastic-rich fraction (density < 2.0 g / cm 3 ).

[0127] Raw material A1 of the present invention

[0128] Scrapped cars are shredded in the scrap car recycling plant. Separated by density separation with a density of ≤1.06g / cm 3 of the plastic-rich fraction.

[0129] Comparison with raw material B

[0130] Mixed automotive plastic waste consisting of fully or mostly intact parts (not shredded, disassembled), for example from repair shops or scrap car recycling companies.

[0131] Comparison with raw material C

[0132] Mixed automotive plastic waste consisting of fully or mostly intact parts (not shredded, disassembled), e.g. from repair shops or scrap car recycling companies. Manual separation of metal-containing parts (e.g. electronic parts) and cables

[0133] Raw materials B1-B2 of the present invention and comparison B3-B4

[0134] The sorting of mixed automotive plastic waste from repair shops is based on the typical application of specific polymers and polymer composites of specific components.

[0135] - Density <1.0g / cm 3 Colorless tanks (e.g. cooling water expansion tanks) are assigned to the polyethylene part. For density < 1.0 g / cm 3The black fuel tank and the black fuel hose portion that distributes the halogenated materials;

[0136] - Dimension > 10 cm along one axis and density < 1.06 g / cm 3 Unpainted exterior parts (e.g. wheel house linings, wheel arches and bumper rails) are specified as PP talc and mineral filled parts. After manual separation of the polyamide parts, the dimensions along one axis > 10 cm and the density of 1.06-1.3 g / cm 3 Unpainted exterior parts such as wheel house liners, wheel arches and bumper rails are designated as ASA, ABS, PC / ABS, POM parts and PA parts according to the material stamp on the part;

[0137] - Dimension > 10 cm along one axis and density 1.06-1.3 g / cm 3 The hood is assigned to the PA section;

[0138] - Dimension > 10 cm along one axis and density < 1.06 g / cm 3 Painted exterior parts (e.g. grilles, door panels, bumpers) are specified as PP talc and mineral filled parts. After manual separation of polyamide parts, the dimensions along one axis > 10 cm and the density 1.06-1.3 g / cm 3 Painted exterior parts (e.g. grilles, door panels, bumpers) are assigned to the ASA, ABS, PC / ABS, POM segments, and to the PA segment based on the material imprint on the part;

[0139] - will have dimensions > 30 cm in each of the two spatial axes (e.g. for underbody protection of the engine) and 1.04-1.13 g / cm 3 The density of the flat unpainted outer part is assigned to the polypropylene fiberglass part;

[0140] - Dimension > 10 cm along one axis and density < 1.06 g / cm 3 Unpainted interior parts (e.g. dashboard carriers, covers) are assigned to the PP talc and mineral filled parts. Interior parts with a post-foamed surface (e.g. dashboard) with a Shore hardness <50 (Shore D), a dimension along one axis >10 cm, and a density of 0.9-1.06 g / cm2 are assigned to the halogenated polymer and electronics parts. 3 ;

[0141] - Density>2.0g / cm 3 The components with a density of 1.3-2.0 g / cm 3 Electronic components, cables and electrical insulation assigned to halogenated polymers, electronic parts;

[0142] - After manual separation of polyamide parts, the dimension along one axis is >10 cm and the density is 1.06-1.3 g / cm 3 The internal parts are assigned to the ASA, ABS, PC / ABS, POM sections, and the material imprint on the parts is assigned to the PA section;

[0143] -Density < 0.88 g / cm 3 The fully foamed and woven components and rubber seals are designated as unknown parts.

[0144] Based on material density (polypropylene 0.91g / cm 3 ; Talc 2.6g / cm 3 ; Glass fiber 2.5g / cm 3 ) Determine the filler content of the PP talc and mineral filled fraction and the PP glass fiber fraction separated as described above.

[0145] The raw material properties averaged over the three samples analyzed are summarized in Table 2.

[0146] Table 2

[0147]

[0148] The feedstock and catalyst were introduced into a reactor unit equipped with a heating unit, a gas discharge unit, a solid discharge unit; a condensation unit and a screw for uniform mixing of the reactor contents during depolymerization. The conditions of the depolymerization performed are summarized in Table 3. The obtained gaseous fraction was further separated into liquid and gaseous depolymerization products by condensation. The amounts of the obtained fractions are also given in Table 3.

[0149] Table 3: Process parameters and mass balance

[0150]

[0151] Referring to the results in Table 3, it can be observed that the tests of the present invention show a high amount of liquid + gas depolymerization products and a lower amount of residue relative to the tests prepared under the same conditions with different feedstocks.

[0152] Liquid depolymerization products from C1, C2 and C4 contain high amounts of heteroatoms and halogens, which makes them unsuitable as cracker feeds.

[0153] The obtained gaseous depolymerization products were further analyzed. The analysis results are summarized in Table 4.

[0154] Table 4 Analysis of pyrolysis gas

[0155]

[0156] Referring to the results in Table 4, it can be observed that the inventive runs 6-7 show the lowest amounts of CO and CO2, low amounts of CH4 combined with the highest amounts of higher alpha olefins such as propylene and butenes and saturated homologues propane and butane.

Claims

1. A method for recycling automobile plastic waste, comprising: (i) sorting the automotive plastic waste (APW) to obtain a plastic waste fraction comprising a mixture of at least 60 wt.% of polyethylene (PE) and polypropylene (PP); (ii) chopping and / or granulating the portion to obtain a plastic material having a bulk density greater than 100 g / l; (iii) depolymerizing the feedstock at 300-500° C. in the optional presence of a catalyst to obtain a gaseous depolymerization product, and (iv) collecting the gaseous depolymerization product and separating it into liquid and gaseous streams.

2. The method according to claim 1, wherein the sorted APW fraction has a PE and PP content higher than 70 wt.%.

3. The method according to any one of the preceding claims, wherein in the sorted APW, the cumulative amount of non-olefin polymers such as polyamide (PA), polycarbonate (PC), polyethylene terephthalate (PET), acrylonitrile styrene acrylate (ASA), polyoxymethylene (POM), acrylonitrile butadiene styrene (ABS) and halogenated polymers is less than 5 wt.%.

4. The process according to any one of the preceding claims, wherein the cumulative amount of non-olefin polymers in the sorted APW is below 3 wt.%, preferably below 2 wt.%.

5. The method of claim 1, wherein step (i) is performed by automated separation technology.

6. The method of claim 1, wherein the APW feedstock is derived from scrap from scrapped cars.

7. The method according to claim 6, comprising producing a density of less than 2.0 g / cm 3 The first sorting step is followed by a separation step for the fraction with a density below 1.06 g / cm 3 An additional density separation step of the polyolefin-rich fraction.

8. The method of claim 1, wherein the APW feedstock is derived from repair shop parts and is sorted based on typical applications for specific polymers, density, and polymer composition of specific components.

9. The method of claim 1, wherein after step (ii), the sorted APW has a density greater than 300 g / cm 3 , more preferably higher than 500g / cm 3 The bulk density.

10. The method according to claim 9, wherein after step (ii), the sorted APW fraction has a particle size of 1-100 mm, preferably 1-20 mm, more preferably 2-10 mm.

11. The process according to claim 1, wherein the depolymerization stage (ii) is carried out in the presence of a catalyst.

12. The method of claim 11, wherein the catalyst comprises an acidic compound deposited on a particulate non-porous support with the aid of a coating agent.

13. The process according to any one of the preceding claims, wherein the gaseous depolymerization product has at least 50 wt.% of the general formula C with n=2-4 n H 2n The content of the compound.

14. The process according to any one of the preceding claims, wherein the liquid depolymerization product has an evaporation residue content of not more than 5 ppm (w) determined according to ASTM D381.

15. A feedstock for a recycling process, the feedstock comprising a sorted automotive plastic waste fraction, the sorted automotive plastic waste fraction comprising: - a mixture of at least 60 wt.% of polyethylene (PE) and polypropylene (PP); - less than 5 wt.% of polymers derived from monomers comprising heteroatoms (non-olefin polymers); and - Less than 1 wt.% of a metal selected from the group consisting of iron, copper, aluminum, magnesium and chromium.

Citation Information

Patent Citations

  • Polymerization catalyst used for producing polyolefins that have excellent combined properties

    EP1290042A1